Teaching through culture: One teacher's use of culturally relevant practices for African American preschoolers. Issue 3 (12th August 2019) - Sturdivant, Toni Denese; Alanís, Iliana
Abstract : Purpose: Oftentimes, attempts at culturally relevant early childhood practices are limited to diverse materials in the physical environment. The purpose of this study is to document the culturally relevant teaching practices, specifically for African American children, within a culturally diverse preschool classroom with a Black teacher. Design/methodology/approach: The researchers used qualitative methodology to answer the following question: How does a Black preschool teacher enact culturally relevant practices for her African American students in a culturally diverse classroom? Data sources included field notes from classroom observations, transcripts from both formal and informal semi-structured interviews with a Master Teacher and photographs. Findings: The authors found that the participant fostered an inclusive classroom community and a classroom environment that reflected the range of human diversity. She was intentional in her integration of culturally representative read alouds and lessons designed to incorporate students' interests. Finally, she engaged families by facilitating their involvement in her curriculum. However, social justice aspects were absent during the time of the study. Originality/value: This paper contributes to the literature in that it documents a high-quality early childhood classroom with a teacher, that is, actively trying to incorporate the cultures of her African American students. Many extant studies provide examples of superficial culturally relevant pedagogy (CRP) being enacting in early childhood classrooms or the focus is not specifically on African American children.